Karakter Menerima Pelajaran dalam Tinjauan Hadis - Yudha Okta Anuhgra; Yuliharti Abbas; Adam Malik Indra; Zulfira Zulfira (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This paper describes the character of receiving lessons contained in the hadith narrated by Bukhari number 77. The purpose of this study is not only to add references for readers but also to increase the understanding of readers, especially educators, regarding the character of receiving lessons from their students in this Bukhari hadith number 77. The method used in this study is a literature study method, by collecting information relevant to the topics discussed through all written sources, both printed and electronic. And also internet searches, namely by searching for information related to the topics discussed via the internet using applications or websites. As a result, in the hadith, there are three types of students' characters in receiving lessons which are likened to fertile soil or earth, barren land, and flat slippery soil. So it can be concluded that the character of students in receiving lessons is divided into three. First, like fertile earth, where they can practice and teach it. Second, like a barren land, where they can teach but are unable to practice. Last, like a flat slippery ground, where they are unable to practice and teach it.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//